Government ownership of banks and corporate maturity mismatch: Evidence from China - Ma, Xiaotian; Liu, Guanchun; Liu, Yuanyuan; He, Feng (Journal of Banking & Finance, 2025)
In the 1990s and the 2000s, many urban credit cooperatives in China were reformed to city commercial banks with the introduction of government ownership. We exploit this bank ownership reform as a quasi-natural experiment to evaluate its impact on corporate maturity mismatch. We find that local firms reduced reliance on short-term debt for investments by obtaining greater long-term credit. The reduction of corporate maturity mismatch is more pronounced if the city has fewer financial resources, or if the firm has greater financial constraints, R&D intensity, or market competition. Local firms’ capital allocation efficiency also increased. Our findings highlight the positive effect of government ownership in enhancing liquidity and promoting growth.